Cilia-driven flows in the brain third ventricle. (17th February 2020) - Eichele, Gregor; Bodenschatz, Eberhard; Ditte, Zuzana; Günther, Ann-Kathrin; Kapoor, Shoba; Wang, Yong; Westendorf, Christian
Abstract : The brain ventricles are interconnected, elaborate cavities that traverse the brain. They are filled with cerebrospinal fluid (CSF) that is, to a large part, produced by the choroid plexus, a secretory epithelium that reaches into the ventricles. CSF is rich in cytokines, growth factors and extracellular vesicles that glide along the walls of ventricles, powered by bundles of motile cilia that coat the ventricular wall. We review the cellular and biochemical properties of the ventral part of the third ventricle that is surrounded by the hypothalamus. In particular, we consider the recently discovered intricate network of cilia-driven flows that characterize this ventricle and discuss the potential physiological significance of this flow for the directional transport of CSF signals to cellular targets located either within the third ventricle or in the adjacent hypothalamic brain parenchyma. Cilia-driven streams of signalling molecules offer an exciting perspective on how fluid-borne signals are dynamically transmitted in the brain. This article is part of the Theo Murphy meeting issue 'Unity and diversity of cilia in locomotion and transport'.